Common Fixed Point Theorems For Weakly Compatible Mappings Satisfying Rational Contractive Conditions In Complete Metric Spaces - Goyal, A.K. (International Journal of Psychosocial Rehabilitation, 2024)
By using notions of compatibility, weak compatibility, and commutativity, Goyal ([5], [6]) proves some common fixed point theorems for six mappings involving rational contractive conditions in complete metric spaces. In this paper, we prove a common fixed point theorem for three pairs of weakly compatible mappings in complete metric spaces satisfying a rational inequality without any continuity requirement, which generalizes several previously known results due to Imdad and Ali [12], Goyal [5], Imdad-Khan [13], Jeong-Rhoades [7], and others.